Soccer injury surveillance and implementation of an injury prevention programme in Rwanda - Nuhu, Assuman (Department of Health and Rehabilitation Sciences, 2018)
Background: There is growing participation in soccer at all levels of sport. Soccer increases the physical and psychological demands on players, which subsequently increase the risk of injuries. There are limited prospective epidemiological studies in Africa, and studies that have been conducted to date often fail to incorporate standardised injury definitions or reporting methods. Therefore, there is an urgent need to conduct epidemiological studies within the context of low to middle-income countries, where resources may be limited, and taking into consideration exposure times to design appropriate preventive measures. Aim: The purpose of the study was to explore the nature and incidence of soccer-related injuries in first division players in Rwanda, and to establish intrinsic risk factors for injuries. Methods: A prospective cohort study was conducted for two seasons. Eleven teams (326 players) and 13 teams (391 players) were followed for the seasons 2014-2015 and 2015-2016. Anthropometric and musculoskeletal screening composed of flexibility tests, strength and endurance, balance and proprioception tests, and lower limb function tests were conducted as well as training and match exposure were recorded. Team medical personnel recorded the location, type, duration and mechanism of time-loss injuries following the suggestion of the International Federation of Football Associations (FIFA). The primary outcome was the incidence of overall, training and match injury as well as body part, type, patterns and severity of injuries. Multivariate model using the Chi-squared Automatic Interaction Detection (CHAID) was used to assess intrinsic predictors of injury. Significance was accepted as p<0.05. Results: There were 455 injuries and approximately 46% of the players were injured in each of the two seasons. The team weighted mean incidence of match injuries was significantly lower during season one (14.2 injuries/ 1000 hours) compared to season two (21.9 injuries/ 1000 hours) (t(22)= -2.092, p=0.048). No difference was observed in the team-weighted incidence for overall and training injuries between the two seasons. There was increased injury incidence with increased acute: chronic training and match workload ratios. Lower extremities were the most frequently affected over the two seasons (80% of all injuries), with the knee joint most commonly injured (28% off all injuries) followed by the ankle joint (25% of all injuries). Ligament strains were the most common form of injury followed by muscle strains and contusions. The most common mechanisms of injury were collisions between players and receiving a tackle. About three quarters of the reported injuries were mild or moderate in severity and injuries to the Achilles tendon lead to the longest median lay-off time. The greatest incidence of injuries was sustained between the 46thand 60thminute of match play. A score of 11cm or less on the Sit and Reach test, more than one year in the current club and a timed hop of more than 2.5 seconds were all associated with injury. Conclusions: The rate of injuries found in this study is lower compared to the studies that reported injuries in adult male at either professional or amateur level. The patterns of training and match injuries, location, type and severity of injuries are similar to previous studies. Flexibility and balance, and coordination emerged as being significant predictors of increased risk of injury. More studies with emphasis on intrinsic and extrinsic factors are needed to attain wider knowledge concerning injuries among soccer players in Africa. Prevention intervention is necessary to minimise the of lower limb injuries.